REFLECTIONS ON CONTEMPORARY LITERATURE PROCESS - Kondakov, B.V.; Popkova, A.A. (Perm Federal Research Centre Journal, 2015)
This paper considers the impact of globalization on the contemporary cultural situation, in particular on the process of how Literature functions in various including peripheral (marginal) forms.